Expanding tracer space for positron emission tomography with high molar activity 18F-labeled α,α-difluoromethylalkanes - Qunchao Zhao; Sanjay Telu; Shuiyu Lu; Victor W. Pike (Nature Communications)
Abstract Positron emission tomography (PET) is an advanced biomedical imaging modality that relies on well-designed radiotracers to report on specific protein targets and processes occurring in living animals and humans. Cyclotron-produced short-lived fluorine-18 (t 1/2 = 109.8 min) is widely used to radiolabel tracers for PET. Herein we aim to expand the chemical space available for PET tracer development to include structures with 18F-labeled α,α-difluoromethylalkyl groups. We report an efficient and broad-scope method for labeling such groups with high molar activities based on a single-step radiofluorination of α-bromo-α-fluoroalkanes. The method is applicable to bioactive compounds and drug-like molecules, and is readily automated for radiotracer production. The unique physical and biochemical features of the α,α-difluoromethyl group can now be exploited in the design of new PET tracers.